Cytotoxicity Potentials of Eleven Bangladeshi Medicinal Plants - Amina Khatun; Mahmudur Rahman; Tania Haque; Md. Mahfizur Rahman; Mahfuja Akter; Subarna Akter; Afrin Jhumur (The Scientific World Journal)
Various forms of cancer are rising all over the world, requiring newer therapy. The quest of anticancer drugs both from natural and synthetic sources is the demand of time. In this study, fourteen extracts of different parts of eleven Bangladeshi medicinal plants which have been traditionally used for the treatment of different types of carcinoma, tumor, leprosy, and diseases associated with cancer were evaluated for their cytotoxicity for the first time. Extraction was conceded using methanol. Phytochemical groups like reducing sugars, tannins, saponins, steroids, gums, flavonoids, and alkaloids were tested using standard chromogenic reagents. Plants were evaluated for cytotoxicity by brine shrimp lethality bioassay using Artemia salina comparing with standard anticancer drug vincristine sulphate. All the extracts showed potent to moderate cytotoxicity ranging from LC50 2 to 115 µg/mL. The highest toxicity was shown by Hygrophila spinosa seeds (LC50=2.93 µg/mL) and the lowest by Litsea glutinosa leaves (LC50=114.71 µg/mL) in comparison with standard vincristine sulphate (LC50=2.04 µg/mL). Among the plants, the plants traditionally used in different cancer and microbial treatments showed highest cytotoxicity. The results support their ethnomedicinal uses and require advanced investigation to elucidate responsible compounds as well as their mode of action.